Cultural and socio-demographic drivers shape seahorse uses in Malaysia: implications for conservation - Reana May Yen Ng; Amy Yee-Hui Then; Adam Chee Ooi Lim (Oryx)
Seahorses Hippocampus spp. are commercially and culturally important to many communities. Although seahorses are widely used in traditional medicine, as curios and as aquarium fishes in Southeast Asia, documentation on the current nature and extent of culturally motivated seahorse uses in Malaysia is lacking. To examine how ethnicity and other socio-demographic drivers shape traditional medicinal use and underlying cultural beliefs involving seahorses, we administered a questionnaire-based survey during March 2021–April 2022 to members of the general public and fishers in Malaysia. Approximately one-fifth (21.0%) of respondents reported consuming seahorses (34.4% of these used seahorses for medicinal purposes, 55.2% for other non-medicinal uses and 10.4% for both types). Consumers of seahorses were from all ethnic groups except for Indigenous groups. In the general public group, medicinal use was more common amongst the Chinese respondents, whereas in the fisher group, other uses were more common amongst the Malay respondents. Amongst the threats facing seahorses, which include overfishing, habitat destruction, bycatch and ocean plastic pollution, only bycatch was perceived as a major threat by most of the general public and fisher respondents. The relatively low prevalence of reported seahorse use amongst Malaysians is an encouraging finding from a conservation perspective. However, the high proportion of non-medicinal uses indicates the need to focus on such other uses to ensure the sustainability of seahorse use in Malaysia.